Environmental Controls on Fallow Carbon Dioxide Flux in a Single‐Crop Rice Paddy, Japan. (5th April 2013) - Ono, K.; Mano, M.; Han, G. H.; Nagai, H.; Yamada, T.; Kobayashi, Y.; Miyata, A.; Inoue, Y.; Lal, R.
Abstract: Soil organic carbon (SOC) is one of the important measures of soil fertility and sustainability in arable lands. With continuous CO2 flux measurements, this study assessed the SOC decomposition and its environmental controls at both half‐hourly and season‐long scales in a single‐crop rice ( Oryza sativa L.) paddy during three fallow periods between 2004 and 2007. Measurements were made on a gray lowland soil sited in eastern Japan using the eddy covariance method. Ecosystem respiration was strongly affected by soil water content measured at 0–0·1 m depth. At 0·5 m 3 m − 3 or more of soil water content, the baseline of ecosystem respiration decreased by 50% compared with that at 0·2 m 3 m − 3 . The effect was quantified at half‐hourly scale using an empirical multiple regression model, together with the soil surface temperature and the time after residue incorporation. At season‐long scale, net biome production, which is equivalent to the change in the SOC pool during the fallow period, was estimated from the flux and ancillary data at 150 g C m − 2 in 2004–2005, 70 g m − 2 in 2005–2006, and 270 g C m − 2 in 2006–2007. Apparently, as much as 46 to 79% of the soil organic matter incorporated (crop residues, ratoon, and stable manure) was decomposed during the fallow period. Precipitation, or associated soil water content, was important for the carbon balance of the field at season‐long scale because of its large interannual variability and relatively low permeability of the paddy soil. Copyright © 2013 John Wiley & Sons, Ltd.